Effects of four soaps on skin trans‐epidermal water loss and erythema index. (29th August 2018) - Khosrowpour, Zeynab; Ahmad Nasrollahi, Saman; Ayatollahi, Azin; Samadi, Aniseh; Firooz, Alireza
Summary: Background: Various tests have been carried out to determine the irritant potential of soaps/cleansers. Objectives: This study was carried out to compare the effects of four different soap formulations on biophysical parameters of the skin, including trans‐epidermal water loss (TEWL) and erythema index. Methods: Four different soap formulations (creamy, glycerin containing, syndet, and traditional alkaline soaps) were studied. Twenty healthy volunteers were enrolled and 8% solutions (W/V) of the soaps made with distilled water, 20% sodium dodecyl sulfate (positive control) and water (negative control) were applied to their volar forearms as a single dose patch test. The patches remained on the sites for 4 hours. The skin TEWL and erythema index were measured before applying the patches and 24 and 72 hours after removal of them using TEWAmeter and Mexameter probes, respectively. Results: Alkaline and creamy soaps caused a significant increase in TEWL 24 hours after patch removal. However, 72 hours after patch removal, this increase was significant only in case of alkaline soap ( P ‐value = 0.002). A decreasing trend in skin erythema was observed 24 and 72 hours after application of syndent, glycerin, and creamy soaps. In case of creamy soap, this decrease was significant 72 hours after patch removal ( P ‐value = 0.006). Conclusion: Traditional alkaline soap increased TEWL and skin erythema, which are signs of prolonged damage to the skin barrier. However, the effects of other formulations were transient, and TEWL returned to baseline at 72 hours. Creamy soap even showed a relative protective effect (decrease in erythema index compared to baseline), probably due to the lanolin content of the formulation.